Analisa Penerimaan Teknologi Cloud Computing pada Infrastruktur Data Center PT. Sentral Link Solutions - Kaka Mulyana; Nita Merlina (LPPM STMIK ANTAR BANGSA, 2018)
Abstract – Utilization of cloud computing by the enterprise information technology has not a new thing anymore because cloud computing technology proven to deliver efficiency in reducing cost in data centers large and complex. However the use of cloud computing technology with different task and functions as virtual information. Be found to the primary three main factors: perceived usefulness, perceived ease of use, and behavioral intention to use. Testing the hypothesis in this research model using a varince-based Partial Least Square (PLS) with trimming model technique, and proven five hypothesis is accepted. There is a relationship that proved significant following: 1) behavioral intention to use and actual technology use, 2) perceived ease of use and behavioral intention to use, 3) perceived ease of use and perceived usefulness, 4) perceived usefulness and actual technology use, 5) perceived usefulness and behavioral intention to use.Intisari – Pemanfaatan teknologi cloud computing oleh perusahaan teknologi informasi sudah bukan hal baru lagi karena teknlogi cloud computing terbukti memberikan efisiensi dalam menurunkan biaya pada pusat data yang besar dan kompleks. Meskipun demikian pemanfaatan teknologi cloud computing dengan tugas dan fungsi yang berbeda dari sebelumnya, yaitu sebagai lingkungan infrastruktur teknologi informasi virtual akan mempengaruhi keputusan perilaku pengguna untuk mengadopsi dan memanfaatkan teknologi tersebut. Terdapat tiga faktor utama, yaitu perceived usefulness, perceived ease of use, dan behavioral intention to use. Pengujian hipotesis dalam model penelitian ini menggunakan variance-based Partial Least Squares (PLS) dengan trimming model, dan terbukti lima hipotesis yang diajukan diterima. Terdapat hubungan berikut yang terbukti signifikan yaitu: 1) behavioral intention to use dengan actual technology use, 2) perceived ease of use dengan behavioral intention to use, 3) perceived ease of use dengan perceived usefulness, 4) perceived usefulness dengan actual technology use, 5) perceived usefulness dengan behavioral intention to use.Kata Kunci: Teknologi, Cloud Computing, Technology Acceptance Model (TAM), Partial Least Square (PLS).